“Postface to a Catalogue on Bronze and Stone Inscriptions” by Li Qingzhao - Dashchenko, Anna (Respectus Philologicus, 2014)
This article presents the first Russian translation of Postface to a Catalogue on Bronze and Stone Inscriptions (In Chinese: 金石录后序) with detailed comments. This postface was written in about 1135 by the outstanding Chinese poetess and the founder of Yi-an style Li Qingzhao (1084–1155). Her work is not just a supplement written to a fundamental catalogue compiled by her husband Zhao Mingcheng – a famous epigraphist, collector of ancient objects of art and high-rank official. Postface is a unique work because it introduces two genres: an epitaph in commemoration of her husband and an autobiographical essay. Moreover, it is the first female autobiography in the history of Chinese literature. The number of hieroglyphs in this text varies from 1866 to 1877 in different editions. We have revealed the distinctive features in Chinese and English traditions of commenting and studying the Postface. Chinese works are characterized by dominance of impressionist evaluations, lack of well-defined analytical categories and background knowledge. In addition, English works are characterized by using different approaches to translation of the dates and the reign periods, and by attention to the certain stories and personalities mentioned in the text for better understanding the biography of Li Qingzhao. Different opinions as to when this Postface was written have been analyzed and we have also presented our point of view to this matter.